ATTITUDES TOWARD VULNERABLE POPULATIONS IN THE TIME OF COVID-19: CRITICAL DISCOURSE ANALYSIS OF GAZETA.PL ONLINE COMMENT SECTIONS - GRZELKA, MICHALINA (Society Register, 2020)
According to the World Health Organization, older people and people with preexisting medical conditions appear to be more vulnerable to becoming severely ill with the COVID-19 virus (World Health Organization 2020). A few journalists (Arielle 2020, Held 2020) have pointed out that in light of the current COVID-19 crisis, vulnerable populations such as elderly people, people with disabilities, and people with preexisting medical conditions have been talked about as if they were “disposable” or “expendable”. Therefore, this study will attempt to examine how vulnerable populations are perceived by Polish public in the context of the global COVID-19 pandemy. In order to achieve that, I will analyze, by the means of critical discourse analysis, comment sections below online articles and editorials covering the topic of the COVID-19 virus on the popular Polish portal Gazeta.pl. In order to narrow down the scope of this study I will only focus on those articles and comments that were published in the week following March 4th 2020 when the first COVID-19 case in Poland was officially confirmed. I believe that this preliminary study will provide useful data for assessing public attitudes toward vulnerable people in times of crisis.